The plane tree and the singing cicadas in Plato’s Phaedrus: the environment of dialogue - Gomes Guimarães, Henrique (Revista Archai, 2023)
This article aims to rethink the meaning of “nature” and the human in Plato, more specifically through some examples contained in the Phaedrus, a rare dialogue further away from the city. Phaedrus and Socrates leave Athens on a path outside the walls, past the Ilisus stream and the breeze of the woods, and end up sitting in the shadows of trees full of singing cicadas. What is the meaning of this scenario in the construction o the text? Is it possible to learn from oak trees or insects? The philosophizing of this dialogue passes through the coolness of the shadows of the trees in the hot summer noon. This sensuous topography through the text reveals the writer Plato wary of the enveloping meaning of the living drama between Phaedrus and Socrates. The audience and participation of natural elements, trees and cicadas in the dialogue reveals an involvement of the discourse with the surrounding atmosphere, a special concern of Socrates in his palinode and in his final prayer to Pan. In this dialogue, more than distinct and removed from nature, we think the human being (and reason) immersed in it - in an attempt to integrate a mythological and dialogical search between river, rock, plants, animals, humans, gods and demigods. The image of an overly rationalist and humanist Plato finds in this text a perspective of an inspired writer, a hybrid poet and philosopher, with a mission to restore language and the city to animal and cosmic life.